Evolutionary Trade-Off between Secondary Sexual Traits and Ejaculates. (December 2017) - Simmons, Leigh W.; Lüpold, Stefan; Fitzpatrick, John L.
Abstract : Recent theoretical models predict that the evolutionary diversification of the weapons and ornaments of pre-mating sexual selection should be influenced by trade-offs with male expenditure on ejaculates. However, the patterns of association between secondary sexual traits and ejaculate expenditure are frequently inconsistent in their support of this prediction. We show why consideration of additional life-history, ecological, and mating-system variables is crucial for the interpretation of associations between secondary sexual traits and ejaculate production. Incorporation of these 'missing variables' provides evidence that interactions between pre- and post-mating sexual selection can underlie broad patterns of diversification in male weapons and ornaments. We call for more experimental and genetic approaches to uncover trade-offs, as well as for studies that consider the costs of mate-searching. Trends: Competition among males for access to mating opportunities is now widely recognized to drive the evolution of exaggerated secondary sexual traits. However, the role of post-mating competition for fertilizations in the evolution of weapons and ornaments has only recently been questioned. Male expenditure on both weapons and ejaculates is costly, and allocation trade-offs between secondary sexual traits and ejaculates are predicted to govern their joint evolution. Empirical support for this expected trade-off remains ambiguous. Consideration of additional ecological, life-history, and mating-system variables can reconcile inconsistent patterns of covariation between secondary sexual traits and ejaculate expenditure, and demonstrate that this trade-off can underlie broad patterns of divergence in weapons and ornaments.